A special protective slag for 2520 heat-resistant stainless steel and its preparation process

By adopting specific formulas and preparation processes in the 2520 heat-resistant stainless steel special protective slag, the problems of reduced fluidity of the protective slag, weakened deoxygenation and weakened desulfurization effect are solved, and the effect of significantly improving fluidity and corrosion resistance is achieved.

CN119282054BActive Publication Date: 2025-04-01LUOYANG KEFENG NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411836412.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-01
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The 2520 heat-resistant stainless steel special protective slag has problems such as decreasing slag fluidity, weakening of deoxygenation and weakening of desulfurization during the smelting process, mainly because the high content of chromium and nickel poses challenges to the performance of the protective slag.

Method used

A protective slag formula including calcium oxide, alumina, zirconium oxide powder, silica, manganese oxide, titanium dioxide, calcium fluoride, stabilizers and rare earth element oxides is used, and a specific preparation process, including co-precipitation method, is prepared by a zirconium oxide powder and depositing alumina and silica composite coating on the magnesium oxide surface.

Benefits of technology

It significantly improves the fluidity and corrosion resistance of the protective slag, enhances its stability and deoxygenation and desulfurization effects at high temperatures, and optimizes the overall performance of the slag.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_10
    Figure SMS_10
Patent Text Reader

Abstract

The present invention relates to the field of protective slag technology, specifically, to a special protective slag for 2520 heat-resistant stainless steel and a preparation process thereof. It comprises the following components: 30-40 parts by weight of calcium oxide, 15-20 parts by weight of aluminum oxide, 8-12 parts by weight of zirconium oxide powder, 5-10 parts by weight of silicon dioxide, 10-15 parts by weight of manganese oxide, 3-5 parts by weight of titanium dioxide, 3-5 parts by weight of calcium fluoride, 8-10 parts by weight of stabilizer and 3-5 parts by weight of rare earth element oxide; the zirconium oxide powder is prepared by coprecipitation of zirconium chloride and yttrium nitrate; the stabilizer is obtained by deposition of aluminum oxide and silicon dioxide on the surface of magnesium oxide; the rare earth element oxide is a mixture of cerium oxide and lanthanum oxide. A layer of aluminum oxide and silicon dioxide composite coating is deposited on the surface of magnesium oxide, forming a dense physical barrier on the surface of magnesium oxide, effectively blocking the erosion of magnesium oxide by harmful components in the slag, and significantly improving the corrosion resistance of magnesium oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of protective slag, and in particular to a special protective slag for 2520 heat-resistant stainless steel and a preparation process thereof. Background Art

[0002] 2520 heat-resistant stainless steel special protective slag is a material specially designed for the production process of 2520 heat-resistant stainless steel, especially a special protective slag used in high-temperature operations such as continuous casting and welding; the main purpose of this protective slag is to improve the quality of the ingot, extend the service life of the refractory material, reduce production costs, and improve the working environment.

[0003] However, the main components of the special protective slag for 2520 heat-resistant stainless steel are about 25% chromium and 20% nickel, which give the steel excellent high-temperature properties, including oxidation resistance and creep resistance. The high content of chromium and nickel will cause certain challenges to the protective slag used in the smelting process, such as decreased slag fluidity and weakened deoxidation and desulfurization effects. In view of this, a special protective slag for 2520 heat-resistant stainless steel and a preparation process thereof are proposed. Summary of the invention

[0004] The object of the present invention is to provide a special protective slag for 2520 heat-resistant stainless steel and a preparation process thereof, so as to solve the problems raised in the above-mentioned background technology.

[0005] To achieve the above-mentioned purpose, the present invention provides a special protective slag for 2520 heat-resistant stainless steel, comprising the following components: 30-40 parts by weight of calcium oxide, 15-20 parts by weight of aluminum oxide, 8-12 parts by weight of zirconium oxide powder, 5-10 parts by weight of silicon dioxide, 10-15 parts by weight of manganese oxide, 3-5 parts by weight of titanium dioxide, 3-5 parts by weight of calcium fluoride, 8-10 parts by weight of a stabilizer and 3-5 parts by weight of a rare earth element oxide; wherein the zirconium oxide powder is prepared by coprecipitation of zirconium chloride and yttrium nitrate; the stabilizer is obtained by depositing aluminum oxide and silicon dioxide on the surface of magnesium oxide; and the rare earth element oxide is a mixture of cerium oxide and lanthanum oxide, and the mixing mass ratio of cerium oxide to lanthanum oxide is 2:1.

[0006] Preferably, the molar ratio of zirconium chloride to yttrium nitrate is 20-26:1, and the prepared zirconium oxide powder contains 3.70-4.76 mol% yttrium oxide; the molar ratio of zirconium chloride to yttrium nitrate is 26:1, and the prepared zirconium oxide powder contains 3.70 mol% yttrium oxide; the molar ratio is 20:1, and the prepared zirconium oxide powder contains 4.76 mol% yttrium oxide; the zirconium oxide material containing 3.70-4.76 mol% yttrium oxide can be transformed into a tetragonal phase or a cubic phase at high temperature, which helps to improve the high temperature resistance of the material.

[0007] Preferably, in the stabilizer, magnesium oxide accounts for 80-90% by weight of the stabilizer; and the molar ratio of aluminum oxide to silicon dioxide is 1.18-1.35:1.

[0008] Preferably, the specific preparation steps of the zirconium oxide powder are:

[0009] Dissolve zirconium chloride and yttrium nitrate in water; adjust the pH value of the solution to the range of 7.0-7.8, so that the salts of zirconium and yttrium are precipitated simultaneously, and the zirconium ions and yttrium ions will combine with the hydroxide ions in the solution to form a hydroxide precipitate that is insoluble in water, namely zirconium hydroxide and yttrium hydroxide; add 14-16M ammonia water at a stirring speed of 360-480rpm to precipitate the salts of zirconium and yttrium, and add ammonia water to make the zirconium and yttrium ions form a more stable precipitate, and the ammonia water can provide additional hydroxide ions to help the incompletely precipitated zirconium and yttrium ions form a more complete zirconium hydroxide and yttrium hydroxide precipitate, ensuring that all zirconium ions and yttrium ions are precipitated from the solution; filter and wash the precipitate, and wash it repeatedly with deionized water until there is no chloride ion and nitrate ion remaining in the washing liquid, and remove the soluble impurity ions attached to the surface of the precipitate, such as unreacted chloride ions, nitrate ions, etc., which may remain if not removed cleanly. In the final product, the purity and performance of the zirconium oxide powder are affected. Deionized water is usually used for washing until these ions are no longer detected in the washing liquid; the precipitate is dried in a drying oven at 60-100°C to remove moisture; the dried precipitate is calcined in a muffle furnace at 500-800°C for 2-4 hours to remove organic matter and form zirconium oxide powder. At high temperatures, zirconium hydroxide and yttrium hydroxide will decompose to form zirconium oxide and yttrium oxide, respectively. These oxides will then interact with each other to form zirconium oxide powder, that is, yttrium-stabilized tetragonal zirconium oxide polycrystalline powder; it is sintered again in a high-temperature furnace at 1400-1600°C for 2-4 hours to form a dense zirconium oxide powder. High-temperature calcination helps to improve the crystallinity of the product, so that the formed zirconium oxide powder has a better crystal structure, which is very important for the subsequent sintering step and can ensure that the final zirconium oxide powder material has good mechanical properties and thermal stability.

[0010] Preferably, the preparation steps of the stabilizer are specifically as follows:

[0011] S1.1, washing the magnesium oxide particles with deionized water and ethanol multiple times to remove surface contaminants, and then drying them in an oven at 60-100°C;

[0012] S1.2, dissolving aluminum nitrate in an ethanol solvent, adding citric acid (to improve the stability of the solution) to prepare an aluminum oxide precursor solution; immersing magnesium oxide particles in the precursor solution for 45-60 minutes to ensure sufficient adsorption; taking out the magnesium oxide particles, rinsing them with deionized water to remove excess precursor solution; heat treating them in a muffle furnace at 500-800°C for 2-4 hours to decompose the precursor and form an aluminum oxide coating;

[0013] S1.3, dissolving tetraethyl orthosilicate in ethanol solvent, adding 15M ammonia water to promote hydrolysis and polycondensation reaction, and preparing a silica precursor solution; immersing magnesium oxide particles on which an aluminum oxide layer has been deposited in the precursor solution for 30-45 minutes to ensure sufficient adsorption; taking out the magnesium oxide particles, rinsing them with deionized water, and removing excess precursor solution; heat treating them in a muffle furnace at 500-800°C for 2-4 hours to decompose the precursor and form a silica coating; forming a stabilizer having a multi-layer composite coating by successively depositing an aluminum oxide layer and a silicon dioxide layer; wherein the aluminum oxide layer and the silicon dioxide layer The siliconized layer can change the composition of the slag, affect the density and viscosity of the slag, help the inclusions to float in the slag, make it easier to separate from the molten metal, and reduce the residual amount of inclusions in the casting; at the same time, it can improve the fluidity of the slag, make it more evenly distributed during the pouring process, and reduce the friction between the ingot and the crystallizer; the formation of the coating helps to form a uniform and stable protective slag film during the continuous casting process, further optimizing the fluidity and distribution of the slag. The composite coating helps to improve the interface compatibility between the slag and the refractory material, reduce the occurrence of interface reactions, and further reduce the risk of slag line erosion.

[0014] Preferably, in S1.2, the amount of citric acid added is 10%-20% of the molar number of aluminum nitrate; and the concentration of the aluminum oxide precursor solution is 0.2-0.3M.

[0015] Preferably, in S1.3, the molar ratio of ammonia water to ethyl orthosilicate solution is 0.18-0.28:1; and the concentration of the silicon dioxide precursor solution is 0.08-0.15M.

[0016] Preferably, the aluminum oxide layer is deposited to a thickness of 9-12 μm; and the silicon dioxide layer is deposited to a thickness of 4-6 μm.

[0017] On the other hand, the present invention provides a preparation process of a special protective slag for 2520 heat-resistant stainless steel, which is used for a special protective slag for 2520 heat-resistant stainless steel as described in any one of the above items. The specific preparation process of the special protective slag for 2520 heat-resistant stainless steel is as follows:

[0018] According to the content requirements of each component in the protective slag formula, the following raw material components are weighed in mass percentage: 30-40 weight parts of calcium oxide, 15-20 weight parts of aluminum oxide, 8-12 weight parts of zirconium oxide powder, 5-10 weight parts of silicon dioxide, 10-15 weight parts of manganese oxide, 3-5 weight parts of titanium dioxide, 3-5 weight parts of calcium fluoride, 8-10 weight parts of stabilizer and 3-5 weight parts of rare earth element oxide, and the above raw materials are mixed evenly; the mixed raw materials are put into a high-temperature furnace to melt to form a fluid slag; the molten protective slag is poured into a mold, cooled and solidified into a shape; the solidified protective slag block is crushed into slag particles, and sieved through a sieve to obtain finished protective slag particles.

[0019] Preferably, the particle size of the finished protective slag particles is 0.28-0.38 mm.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. In the special protective slag for 2520 heat-resistant stainless steel and its preparation process, a layer of alumina and silica composite coating is deposited on the surface of magnesium oxide, forming a dense physical barrier on the surface of magnesium oxide, effectively blocking the corrosion of harmful components in the slag to magnesium oxide, and significantly improving the corrosion resistance of magnesium oxide; at the same time, the selectivity and permeability of the coating allow magnesium oxide to still react with components (such as sulfur) in the slag when necessary, maintaining its activity in desulfurization and impurity removal; alumina and silica have a high melting point and good thermal stability, and the composite coating significantly improves the stability of magnesium oxide at high temperatures, preventing it from decomposing or deteriorating, and the composite protective modified magnesium oxide improves the corrosion resistance and fluidity of the slag, and optimizes the overall performance of the slag;

[0022] 2. In the special protective slag for 2520 heat-resistant stainless steel and its preparation process, the zirconium oxide powder is composed of zirconium oxide and yttria. Yttria doping can stabilize the tetragonal phase of zirconium oxide and keep its structure stable at high temperature. For the special protective slag for 2520 heat-resistant stainless steel, it has excellent fracture toughness and thermal stability, which helps to protect the slag line from erosion. The zirconium oxide powder has good high-temperature stability and can maintain its physical and chemical properties unchanged even under extremely high temperature conditions, ensuring the effectiveness and stability of the protective slag throughout the casting or welding process. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0024] The special protective slag for 2520 heat-resistant stainless steel of the present invention comprises the following components: 30-40 parts by weight of calcium oxide, 15-20 parts by weight of aluminum oxide, 8-12 parts by weight of zirconium oxide powder, 5-10 parts by weight of silicon dioxide, 10-15 parts by weight of manganese oxide, 3-5 parts by weight of titanium dioxide, 3-5 parts by weight of calcium fluoride, 8-10 parts by weight of a stabilizer and 3-5 parts by weight of a rare earth element oxide; the rare earth element oxide is a mixture of cerium oxide and lanthanum oxide, and the mixing mass ratio of cerium oxide to lanthanum oxide is 2:1.

[0025] The specific preparation steps of zirconium oxide powder are as follows:

[0026] Dissolve zirconium chloride and yttrium nitrate in water; adjust the pH value of the solution to the range of 7.0-7.8 to precipitate zirconium and yttrium salts simultaneously; add 14-16M ammonia water at a stirring speed of 360-480rpm to precipitate zirconium and yttrium salts; filter and wash the precipitate, and repeatedly wash with deionized water until no chloride ions and nitrate ions remain in the washing liquid; dry the precipitate in a drying oven at 60-100°C to remove moisture; calcine the dried precipitate in a muffle furnace at 500-800°C for 2-4 hours to remove organic matter and form zirconium oxide powder; and sinter again in a high-temperature furnace at 1400-1600°C for 2-4 hours to form a dense zirconium oxide powder, specifically, the zirconium oxide powder is a tetragonal zirconium oxide polycrystalline powder composed of zirconium oxide and yttrium oxide.

[0027] Example 1: A specific preparation process of a special protective slag for 2520 heat-resistant stainless steel is as follows:

[0028] According to the requirements of the content of each component in the protective slag formula, the following raw material components of calcium oxide 35 weight parts, aluminum oxide 15 weight parts, zirconium oxide powder 8 weight parts, silicon dioxide 8 weight parts, manganese oxide 13 weight parts, titanium dioxide 3 weight parts, calcium fluoride 3 weight parts, stabilizer 8 weight parts and rare earth element oxide 3 weight parts are weighed respectively, and the above raw materials are mixed evenly; the mixed raw materials are put into a high-temperature furnace for melting to form a fluid slag; the molten protective slag is poured into a mold, cooled and solidified; the solidified protective slag block is crushed into slag particles with a particle size of 0.36 mm, and sieved through a sieve to obtain finished protective slag particles; wherein the zirconium oxide powder is prepared by coprecipitation of zirconium chloride and yttrium nitrate, and the molar ratio of zirconium chloride to yttrium nitrate is 20:1; the stabilizer is obtained by depositing aluminum oxide and silicon dioxide on the surface of magnesium oxide, and magnesium oxide accounts for 80% of the weight of the stabilizer; the molar ratio of aluminum oxide to silicon dioxide is 1.25:1.

[0029] Furthermore, the preparation steps of the stabilizer are specifically as follows:

[0030] S1.1, washing the magnesium oxide particles with deionized water and ethanol several times to remove surface contaminants, and then drying them in an oven at 90°C;

[0031] S1.2, dissolving aluminum nitrate in ethanol solvent, adding citric acid to prepare an aluminum oxide precursor solution with a concentration of 0.25M, wherein the amount of citric acid added is 10% of the molar number of aluminum nitrate; immersing magnesium oxide particles in the precursor solution for 60 minutes; taking out the magnesium oxide particles, rinsing them with deionized water to remove excess precursor solution; heat treating them in a muffle furnace at 600°C for 3 hours to decompose the precursor and form an aluminum oxide coating;

[0032] S1.3. Dissolve tetraethyl orthosilicate in ethanol solvent, add 15M ammonia water to prepare a silica precursor solution with a concentration of 0.12M, and the molar ratio of ammonia water to tetraethyl orthosilicate is 0.18:1; immerse the magnesium oxide particles on which an aluminum oxide layer has been deposited in the precursor solution and keep it for 40 minutes; take out the magnesium oxide particles, rinse them with deionized water to remove excess precursor solution; heat treat them in a muffle furnace at 800°C for 3 hours to decompose the precursor and form a silica coating; by successively obtaining an aluminum oxide layer with a deposition thickness of 9μm and a silica layer with a deposition thickness of 4μm, a stabilizer with a multi-layer composite coating is formed.

[0033] Example 2: The specific preparation process of a preparation process of a special protective slag for 2520 heat-resistant stainless steel is as follows:

[0034] According to the content requirements of each component in the protective slag formula, the following raw material components of calcium oxide 35 weight parts, aluminum oxide 15 weight parts, zirconium oxide powder 10 weight parts, silicon dioxide 8 weight parts, manganese oxide 13 weight parts, titanium dioxide 3 weight parts, calcium fluoride 3 weight parts, stabilizer 8 weight parts and rare earth element oxide 3 weight parts are weighed respectively, and the above raw materials are mixed evenly; the mixed raw materials are put into a high-temperature furnace for melting to form a fluid slag; the molten protective slag is poured into a mold, cooled and solidified; the solidified protective slag block is crushed into slag particles with a particle size of 0.36 mm, and sieved through a sieve to obtain finished protective slag particles; wherein the zirconium oxide powder is prepared by coprecipitation of zirconium chloride and yttrium nitrate, and the molar ratio of zirconium chloride to yttrium nitrate is 20:1; the stabilizer is obtained by deposition of aluminum oxide and silicon dioxide on the surface of magnesium oxide, and magnesium oxide accounts for 80% of the weight of the stabilizer; the molar ratio of aluminum oxide to silicon dioxide is 1.25:1.

[0035] Furthermore, the preparation steps of the stabilizer are specifically as follows:

[0036] S1.1, washing the magnesium oxide particles with deionized water and ethanol several times to remove surface contaminants, and then drying them in an oven at 90°C;

[0037] S1.2, dissolving aluminum nitrate in ethanol solvent, adding citric acid to prepare an aluminum oxide precursor solution with a concentration of 0.25M, wherein the amount of citric acid added is 10% of the molar number of aluminum nitrate; immersing magnesium oxide particles in the precursor solution for 60 minutes; taking out the magnesium oxide particles, rinsing them with deionized water to remove excess precursor solution; heat treating them in a muffle furnace at 600°C for 3 hours to decompose the precursor and form an aluminum oxide coating;

[0038] S1.3. Dissolve tetraethyl orthosilicate in ethanol solvent, add 15M ammonia water to prepare a silica precursor solution with a concentration of 0.12M, and the molar ratio of ammonia water to tetraethyl orthosilicate is 0.18:1; immerse the magnesium oxide particles on which an aluminum oxide layer has been deposited in the precursor solution and keep it for 40 minutes; take out the magnesium oxide particles, rinse them with deionized water to remove excess precursor solution; heat treat them in a muffle furnace at 800°C for 3 hours to decompose the precursor and form a silica coating; by successively obtaining an aluminum oxide layer with a deposition thickness of 9μm and a silica layer with a deposition thickness of 4μm, a stabilizer with a multi-layer composite coating is formed.

[0039] Example 3: The specific preparation process of a preparation process of a special protective slag for 2520 heat-resistant stainless steel is as follows:

[0040] According to the content requirements of each component in the protective slag formula, the following raw material components of calcium oxide 35 weight parts, aluminum oxide 15 weight parts, zirconium oxide powder 12 weight parts, silicon dioxide 8 weight parts, manganese oxide 13 weight parts, titanium dioxide 3 weight parts, calcium fluoride 3 weight parts, stabilizer 8 weight parts and rare earth element oxide 3 weight parts are weighed respectively, and the above raw materials are mixed evenly; the mixed raw materials are put into a high-temperature furnace for melting to form a fluid slag; the molten protective slag is poured into a mold, cooled and solidified; the solidified protective slag block is crushed into slag particles with a particle size of 0.36 mm, and sieved through a sieve to obtain finished protective slag particles; wherein the zirconium oxide powder is prepared by coprecipitation of zirconium chloride and yttrium nitrate, and the molar ratio of zirconium chloride to yttrium nitrate is 20:1; the stabilizer is obtained by deposition of aluminum oxide and silicon dioxide on the surface of magnesium oxide, and magnesium oxide accounts for 80% of the weight of the stabilizer; the molar ratio of aluminum oxide to silicon dioxide is 1.25:1.

[0041] Furthermore, the preparation steps of the stabilizer are specifically as follows:

[0042] S1.1, washing the magnesium oxide particles with deionized water and ethanol several times to remove surface contaminants, and then drying them in an oven at 90°C;

[0043] S1.2, dissolving aluminum nitrate in ethanol solvent, adding citric acid to prepare an aluminum oxide precursor solution with a concentration of 0.25M, wherein the amount of citric acid added is 10% of the molar number of aluminum nitrate; immersing magnesium oxide particles in the precursor solution for 60 minutes; taking out the magnesium oxide particles, rinsing them with deionized water to remove excess precursor solution; heat treating them in a muffle furnace at 600°C for 3 hours to decompose the precursor and form an aluminum oxide coating;

[0044] S1.3. Dissolve tetraethyl orthosilicate in ethanol solvent, add 15M ammonia water to prepare a silica precursor solution with a concentration of 0.12M, and the molar ratio of ammonia water to tetraethyl orthosilicate is 0.18:1; immerse the magnesium oxide particles on which an aluminum oxide layer has been deposited in the precursor solution and keep it for 40 minutes; take out the magnesium oxide particles, rinse them with deionized water to remove excess precursor solution; heat treat them in a muffle furnace at 800°C for 3 hours to decompose the precursor and form a silica coating; by successively obtaining an aluminum oxide layer with a deposition thickness of 9μm and a silica layer with a deposition thickness of 4μm, a stabilizer with a multi-layer composite coating is formed.

[0045] Example 4: The specific preparation process of a preparation process of a special protective slag for 2520 heat-resistant stainless steel is as follows:

[0046] According to the content requirements of each component in the protective slag formula, the following raw material components of calcium oxide 35 weight parts, aluminum oxide 15 weight parts, zirconium oxide powder 10 weight parts, silicon dioxide 8 weight parts, manganese oxide 13 weight parts, titanium dioxide 3 weight parts, calcium fluoride 3 weight parts, stabilizer 10 weight parts and rare earth element oxide 3 weight parts are weighed respectively, and the above raw materials are mixed evenly; the mixed raw materials are put into a high-temperature furnace for melting to form a fluid slag; the molten protective slag is poured into a mold, cooled and solidified; the solidified protective slag block is crushed into slag particles with a particle size of 0.36 mm, and sieved through a sieve to obtain finished protective slag particles; wherein the zirconium oxide powder is prepared by coprecipitation of zirconium chloride and yttrium nitrate, and the molar ratio of zirconium chloride to yttrium nitrate is 20:1; the stabilizer is obtained by depositing aluminum oxide and silicon dioxide on the surface of magnesium oxide, and magnesium oxide accounts for 80% of the weight of the stabilizer; the molar ratio of aluminum oxide to silicon dioxide is 1.25:1.

[0047] Furthermore, the preparation steps of the stabilizer are specifically as follows:

[0048] S1.1, washing the magnesium oxide particles with deionized water and ethanol several times to remove surface contaminants, and then drying them in an oven at 90°C;

[0049] S1.2, dissolving aluminum nitrate in ethanol solvent, adding citric acid to prepare an aluminum oxide precursor solution with a concentration of 0.25M, wherein the amount of citric acid added is 10% of the molar number of aluminum nitrate; immersing magnesium oxide particles in the precursor solution for 60 minutes; taking out the magnesium oxide particles, rinsing them with deionized water to remove excess precursor solution; heat treating them in a muffle furnace at 600°C for 3 hours to decompose the precursor and form an aluminum oxide coating;

[0050] S1.3. Dissolve tetraethyl orthosilicate in ethanol solvent, add 15M ammonia water to prepare a silica precursor solution with a concentration of 0.12M, and the molar ratio of ammonia water to tetraethyl orthosilicate is 0.18:1; immerse the magnesium oxide particles on which an aluminum oxide layer has been deposited in the precursor solution and keep it for 40 minutes; take out the magnesium oxide particles, rinse them with deionized water to remove excess precursor solution; heat treat them in a muffle furnace at 800°C for 3 hours to decompose the precursor and form a silica coating; by successively obtaining an aluminum oxide layer with a deposition thickness of 9μm and a silica layer with a deposition thickness of 4μm, a stabilizer with a multi-layer composite coating is formed.

[0051] Example 5: The specific preparation process of a preparation process of a special protective slag for 2520 heat-resistant stainless steel is as follows:

[0052] According to the content requirements of each component in the protective slag formula, the following raw material components of calcium oxide 35 weight parts, aluminum oxide 15 weight parts, zirconium oxide powder 10 weight parts, silicon dioxide 8 weight parts, manganese oxide 13 weight parts, titanium dioxide 3 weight parts, calcium fluoride 3 weight parts, stabilizer 11 weight parts and rare earth element oxide 3 weight parts are weighed respectively, and the above raw materials are mixed evenly; the mixed raw materials are put into a high-temperature furnace for melting to form a fluid slag; the molten protective slag is poured into a mold, cooled and solidified; the solidified protective slag block is crushed into slag particles with a particle size of 0.36 mm, and sieved through a sieve to obtain finished protective slag particles; wherein the zirconium oxide powder is prepared by coprecipitation of zirconium chloride and yttrium nitrate, and the molar ratio of zirconium chloride to yttrium nitrate is 20:1; the stabilizer is obtained by depositing aluminum oxide and silicon dioxide on the surface of magnesium oxide, and magnesium oxide accounts for 80% of the weight of the stabilizer; the molar ratio of aluminum oxide to silicon dioxide is 1.25:1.

[0053] Furthermore, the preparation steps of the stabilizer are specifically as follows:

[0054] S1.1, washing the magnesium oxide particles with deionized water and ethanol several times to remove surface contaminants, and then drying them in an oven at 90°C;

[0055] S1.2, dissolving aluminum nitrate in ethanol solvent, adding citric acid to prepare an aluminum oxide precursor solution with a concentration of 0.25M, wherein the amount of citric acid added is 10% of the molar number of aluminum nitrate; immersing magnesium oxide particles in the precursor solution for 60 minutes; taking out the magnesium oxide particles, rinsing them with deionized water to remove excess precursor solution; heat treating them in a muffle furnace at 600°C for 3 hours to decompose the precursor and form an aluminum oxide coating;

[0056] S1.3. Dissolve tetraethyl orthosilicate in ethanol solvent, add 15M ammonia water to prepare a silica precursor solution with a concentration of 0.12M, and the molar ratio of ammonia water to tetraethyl orthosilicate is 0.18:1; immerse the magnesium oxide particles on which an aluminum oxide layer has been deposited in the precursor solution and keep it for 40 minutes; take out the magnesium oxide particles, rinse them with deionized water to remove excess precursor solution; heat treat them in a muffle furnace at 800°C for 3 hours to decompose the precursor and form a silica coating; by successively obtaining an aluminum oxide layer with a deposition thickness of 9μm and a silica layer with a deposition thickness of 4μm, a stabilizer with a multi-layer composite coating is formed.

[0057] Example 6: The specific preparation process of a preparation process of a special protective slag for 2520 heat-resistant stainless steel is as follows:

[0058] According to the requirements of the content of each component in the protective slag formula, the following raw material components of calcium oxide 35 weight parts, aluminum oxide 15 weight parts, zirconium oxide powder 10 weight parts, silicon dioxide 8 weight parts, manganese oxide 13 weight parts, titanium dioxide 3 weight parts, calcium fluoride 3 weight parts, stabilizer 12 weight parts and rare earth element oxide 3 weight parts are weighed respectively, and the above raw materials are mixed evenly; the mixed raw materials are put into a high-temperature furnace for melting to form a fluid slag; the molten protective slag is poured into a mold, cooled and solidified; the solidified protective slag block is crushed into slag particles with a particle size of 0.36 mm, and sieved through a sieve to obtain finished protective slag particles; wherein the zirconium oxide powder is prepared by coprecipitation of zirconium chloride and yttrium nitrate, and the molar ratio of zirconium chloride to yttrium nitrate is 20:1; the stabilizer is obtained by depositing aluminum oxide and silicon dioxide on the surface of magnesium oxide, and magnesium oxide accounts for 80% of the weight of the stabilizer; the molar ratio of aluminum oxide to silicon dioxide is 1.25:1.

[0059] Furthermore, the preparation steps of the stabilizer are specifically as follows:

[0060] S1.1, washing the magnesium oxide particles with deionized water and ethanol several times to remove surface contaminants, and then drying them in an oven at 90°C;

[0061] S1.2, dissolving aluminum nitrate in ethanol solvent, adding citric acid to prepare an aluminum oxide precursor solution with a concentration of 0.25M, wherein the amount of citric acid added is 10% of the molar number of aluminum nitrate; immersing magnesium oxide particles in the precursor solution for 60 minutes; taking out the magnesium oxide particles, rinsing them with deionized water to remove excess precursor solution; heat treating them in a muffle furnace at 600°C for 3 hours to decompose the precursor and form an aluminum oxide coating;

[0062] S1.3. Dissolve tetraethyl orthosilicate in ethanol solvent, add 15M ammonia water to prepare a 0.12M silica precursor solution, and the molar ratio of ammonia water to tetraethyl orthosilicate is 0.18:1; immerse the magnesium oxide particles on which an aluminum oxide layer has been deposited in the precursor solution and keep it for 40 minutes; take out the magnesium oxide particles, rinse them with deionized water to remove excess precursor solution; heat treat them in a muffle furnace at 800°C for 3 hours to decompose the precursor and form a silicon oxide coating; by successively obtaining an aluminum oxide layer with a deposition thickness of 9μm and a silicon dioxide layer with a deposition thickness of 4μm, a stabilizer with a multi-layer composite coating is formed.

[0063] Example 7: The specific preparation process of a preparation process of a special protective slag for 2520 heat-resistant stainless steel is as follows:

[0064] According to the content requirements of each component in the protective slag formula, the following raw material components of calcium oxide 35 weight parts, aluminum oxide 15 weight parts, zirconium oxide powder 12 weight parts, silicon dioxide 8 weight parts, manganese oxide 13 weight parts, titanium dioxide 3 weight parts, calcium fluoride 3 weight parts, stabilizer 10 weight parts and rare earth element oxide 3 weight parts are weighed respectively, and the above raw materials are mixed evenly; the mixed raw materials are put into a high-temperature furnace for melting to form a fluid slag; the molten protective slag is poured into a mold, cooled and solidified; the solidified protective slag block is crushed into slag particles with a particle size of 0.36 mm, and sieved through a sieve to obtain finished protective slag particles; wherein the zirconium oxide powder is prepared by coprecipitation of zirconium chloride and yttrium nitrate, and the molar ratio of zirconium chloride to yttrium nitrate is 25:1; the stabilizer is obtained by depositing aluminum oxide and silicon dioxide on the surface of magnesium oxide, and magnesium oxide accounts for 80% of the weight of the stabilizer; the molar ratio of aluminum oxide to silicon dioxide is 1.25:1.

[0065] Furthermore, the preparation steps of the stabilizer are specifically as follows:

[0066] S1.1, washing the magnesium oxide particles with deionized water and ethanol several times to remove surface contaminants, and then drying them in an oven at 90°C;

[0067] S1.2, dissolving aluminum nitrate in ethanol solvent, adding citric acid to prepare an aluminum oxide precursor solution with a concentration of 0.25M, wherein the amount of citric acid added is 10% of the molar number of aluminum nitrate; immersing magnesium oxide particles in the precursor solution for 60 minutes; taking out the magnesium oxide particles, rinsing with deionized water to remove excess precursor solution; heat treating in a muffle furnace at 600°C for 3 hours to decompose the precursor and form an aluminum oxide coating;

[0068] S1.3. Dissolve tetraethyl orthosilicate in ethanol solvent, add 15M ammonia water to prepare a silica precursor solution with a concentration of 0.12M, and the molar ratio of ammonia water to tetraethyl orthosilicate is 0.18:1; immerse the magnesium oxide particles on which an aluminum oxide layer has been deposited in the precursor solution and keep it for 40 minutes; take out the magnesium oxide particles, rinse them with deionized water to remove excess precursor solution; heat treat them in a muffle furnace at 800°C for 3 hours to decompose the precursor and form a silica coating; by successively obtaining an aluminum oxide layer with a deposition thickness of 9μm and a silica layer with a deposition thickness of 4μm, a stabilizer with a multi-layer composite coating is formed.

[0069] Example 8: The specific preparation process of a preparation process of a special protective slag for 2520 heat-resistant stainless steel is as follows:

[0070] According to the content requirements of each component in the protective slag formula, the following raw material components of calcium oxide 35 weight parts, aluminum oxide 15 weight parts, zirconium oxide powder 12 weight parts, silicon dioxide 8 weight parts, manganese oxide 13 weight parts, titanium dioxide 3 weight parts, calcium fluoride 3 weight parts, stabilizer 10 weight parts and rare earth element oxide 3 weight parts are weighed respectively, and the above raw materials are mixed evenly; the mixed raw materials are put into a high-temperature furnace for melting to form a fluid slag; the molten protective slag is poured into a mold, cooled and solidified; the solidified protective slag block is crushed into slag particles with a particle size of 0.25 mm, and sieved through a sieve to obtain finished protective slag particles; wherein the zirconium oxide powder is prepared by coprecipitation of zirconium chloride and yttrium nitrate, and the molar ratio of zirconium chloride to yttrium nitrate is 25:1; the stabilizer is obtained by depositing aluminum oxide and silicon dioxide on the surface of magnesium oxide, and magnesium oxide accounts for 88% of the weight of the stabilizer; the molar ratio of aluminum oxide to silicon dioxide is 1.30:1.

[0071] Furthermore, the preparation steps of the stabilizer are specifically as follows:

[0072] S1.1, washing the magnesium oxide particles with deionized water and ethanol several times to remove surface contaminants, and then drying them in an oven at 90°C;

[0073] S1.2, dissolving aluminum nitrate in ethanol solvent, adding citric acid to prepare an aluminum oxide precursor solution with a concentration of 0.25M, wherein the amount of citric acid added is 15% of the molar number of aluminum nitrate; immersing magnesium oxide particles in the precursor solution for 60 minutes; taking out the magnesium oxide particles, rinsing them with deionized water to remove excess precursor solution; heat treating them in a muffle furnace at 600°C for 3 hours to decompose the precursor and form an aluminum oxide coating;

[0074] S1.3. Dissolve tetraethyl orthosilicate in ethanol solvent, add 15M ammonia water to prepare a 0.15M silica precursor solution, and the molar ratio of ammonia water to tetraethyl orthosilicate is 0.28:1; immerse the magnesium oxide particles on which an aluminum oxide layer has been deposited in the precursor solution and keep it for 40 minutes; take out the magnesium oxide particles, rinse them with deionized water to remove excess precursor solution; heat treat them in a muffle furnace at 800°C for 3 hours to decompose the precursor and form a silica coating; by successively obtaining an aluminum oxide layer with a deposition thickness of 9μm and a silica layer with a deposition thickness of 6μm, a stabilizer with a multi-layer composite coating is formed.

[0075] Example 9: A preparation process of a special protective slag for 2520 heat-resistant stainless steel, the specific preparation process is as follows:

[0076] According to the requirements of the content of each component in the protective slag formula, the following raw material components of calcium oxide 40 weight parts, aluminum oxide 20 weight parts, zirconium oxide powder 12 weight parts, silicon dioxide 10 weight parts, manganese oxide 15 weight parts, titanium dioxide 5 weight parts, calcium fluoride 5 weight parts, stabilizer 10 weight parts and rare earth element oxide 5 weight parts are weighed respectively, and the above raw materials are mixed evenly; the mixed raw materials are put into a high-temperature furnace for melting to form a fluid slag; the molten protective slag is poured into a mold, cooled and solidified; the solidified protective slag block is crushed into slag particles with a particle size of 0.25 mm, and sieved through a sieve to obtain finished protective slag particles; wherein the zirconium oxide powder is prepared by coprecipitation of zirconium chloride and yttrium nitrate, and the molar ratio of zirconium chloride to yttrium nitrate is 25:1; the stabilizer is obtained by deposition of aluminum oxide and silicon dioxide on the surface of magnesium oxide, and magnesium oxide accounts for 88% of the weight of the stabilizer; the molar ratio of aluminum oxide to silicon dioxide is 1.30:1.

[0077] Furthermore, the preparation steps of the stabilizer are specifically as follows:

[0078] S1.1, washing the magnesium oxide particles with deionized water and ethanol several times to remove surface contaminants, and then drying them in an oven at 90°C;

[0079] S1.2, dissolving aluminum nitrate in ethanol solvent, adding citric acid to prepare an aluminum oxide precursor solution with a concentration of 0.25M, wherein the amount of citric acid added is 15% of the molar number of aluminum nitrate; immersing magnesium oxide particles in the precursor solution for 60 minutes; taking out the magnesium oxide particles, rinsing them with deionized water to remove excess precursor solution; heat treating them in a muffle furnace at 600°C for 3 hours to decompose the precursor and form an aluminum oxide coating;

[0080] S1.3. Dissolve tetraethyl orthosilicate in ethanol solvent, add 15M ammonia water to prepare a 0.15M silica precursor solution, and the molar ratio of ammonia water to tetraethyl orthosilicate is 0.28:1; immerse the magnesium oxide particles on which an aluminum oxide layer has been deposited in the precursor solution and keep it for 40 minutes; take out the magnesium oxide particles, rinse them with deionized water to remove excess precursor solution; heat treat them in a muffle furnace at 800°C for 3 hours to decompose the precursor and form a silica coating; by successively obtaining an aluminum oxide layer with a deposition thickness of 10μm and a silica layer with a deposition thickness of 6μm, a stabilizer with a multi-layer composite coating is formed.

[0081] Comparative Example 1: The method of Example 8 was adopted, and zirconium oxide was directly used as a component for preparing special protective slag for 2520 heat-resistant stainless steel, without using zirconium oxide powder prepared by coprecipitation of zirconium chloride and yttrium nitrate.

[0082] Comparative Example 2: The method of Example 8 was adopted to directly remove zirconium oxide from the components for preparing the special protective slag for 2520 heat-resistant stainless steel.

[0083] Comparative Example 3: The method of Example 8 was adopted, but the stabilizer was not subjected to surface deposition treatment on magnesium oxide by aluminum oxide and silicon dioxide, and magnesium oxide was directly used as the stabilizer.

[0084] The performance index inspection items and inspection standards of 2520 heat-resistant stainless steel obtained by adding 2520 heat-resistant stainless steel special protective slag prepared by zirconium oxide powder and stabilizer in the preparation process of 2520 heat-resistant stainless steel and by using 2520 heat-resistant stainless steel special protective slag are as follows:

[0085] Under laboratory conditions, the actual production environment is simulated, the weight loss of the furnace lining material is measured over a certain period of time, and the erosion rate is calculated:

[0086] The erosion rate is calculated by measuring the weight loss of the furnace lining material in a certain period of time, and then the corrosion resistance of the protective slag is judged and the corrosion resistance of the protective slag is evaluated; a 2520 heat-resistant stainless steel sample obtained by using a special protective slag for 2520 heat-resistant stainless steel is selected as the furnace lining material, with a size of 10mm×10mm×100mm, and the initial weight of the sample is weighed using a precision balance , record it, grind the surface of the sample flat, clean it, and remove surface impurities; put the sample into a high-temperature furnace, set the temperature to 1400-1500°C, simulate the high temperature environment during continuous casting; evenly cover the surface of the sample with a layer of protective slag with a thickness of about 1-2mm, and record the start time of the test ; Keep the test time under high temperature conditions for 1 hour and record the end time of the test After the test, the sample was cooled naturally to room temperature and the weight of the sample after the test was measured using a precision balance. ; Calculate the weight loss of the sample before and after the test , calculate the erosion rate , ,in, If the erosion rate If it is less than 0.5 mg / h, the protective slag is considered to have good corrosion resistance; the above method can be used to accurately evaluate the corrosion resistance of the protective slag under high temperature conditions.

[0087] The fluidity of slag is one of the important indicators for evaluating the performance of protective slag, especially in the continuous casting process. Good fluidity can ensure that the protective slag evenly covers the molten steel surface, reduce the secondary oxidation of the molten steel, and improve the stability of the continuous casting process and the quality of the final product. The performance index inspection items and inspection standards for 2520 heat-resistant stainless steel special protective slag are as follows:

[0088] Take a certain amount of mold slag sample, ensure that the sample is uniform, and heat the sample to the required test temperature, usually between 1200-1400°C; put the sample into a viscometer and record the viscosity values ​​at different temperatures; the viscosity of the slag should be within an appropriate range, usually between 1000-2000mPa·s to ensure that the slag has good fluidity and coverage; by evaluating the fluidity of the slag, ensure that it can effectively cover the molten steel surface during the continuous casting process, reduce the secondary oxidation of the molten steel, and improve the stability of the continuous casting process and the quality of the final product.

[0089] The slag adsorption capacity was tested with reference to GB / T 24529: Testing standard for the adsorption performance of protective slag formulated by the China National Standards Committee. During the continuous casting process, good adsorption capacity can effectively remove non-metallic inclusions and harmful elements in molten steel, improve the purity of molten steel and the quality of the final product. The method and standard for the slag adsorption capacity are as follows: take protective slag samples and molten steel samples containing non-metallic inclusions; put the molten steel samples into a high-temperature furnace and set the temperature to 1400-1500°C to simulate the high-temperature environment during the continuous casting process; add protective slag evenly to the molten steel sample through a protective slag injection device, take samples at different time points, separate the protective slag and molten steel, observe the inclusions on the surface of the protective slag, detect the type and quantity of inclusions, and compare the content of inclusions in the molten steel before and after adsorption to calculate the removal rate; among which, the removal rate of inclusions should reach more than 90% to ensure that the protective slag can continuously and effectively adsorb inclusions during the continuous casting process.

[0090] The performance data of 2520 heat-resistant stainless steel prepared by the special protective slag for 2520 heat-resistant stainless steel of the above-mentioned Examples 1-9 and Comparative Examples 1-3 are shown in Table 1:

[0091] Table 1 Performance data of 2520 heat-resistant stainless steel of Examples 1-9 and Comparative Examples 1-3

[0092]

[0093] The above data fully show that Examples 1-9 are compared with Comparative Examples 1-3, as follows:

[0094] It can be seen from Examples 1-3 that when other components in the protective slag for 2520 heat-resistant stainless steel remain unchanged and the weight of zirconium oxide powder continues to increase, the erosion rate of the protective slag significantly decreases, the slag viscosity continues to decrease, and the removal rate of inclusions continues to increase.

[0095] Among them, zirconium oxide in zirconium oxide powder can improve the refractoriness and thermal stability of slag, help protect the slag line from erosion, zirconium oxide powder has good high-temperature stability, even under extremely high temperature conditions can maintain its physical and chemical properties unchanged, ensure the effectiveness and stability of the protective slag in the entire casting process, zirconium oxide powder is composed of zirconium oxide and yttrium oxide, yttrium oxide doping can stabilize the tetragonal phase of zirconia, can also maintain its structural stability at high temperatures, for 2520 heat-resistant stainless steel special protective slag, so that it has excellent fracture toughness and thermal stability.

[0096] Because zirconium oxide powder has good corrosion resistance, it can also effectively prevent chemical reactions between molten metal and mold materials, reduce pollution, and improve the purity and surface quality of castings.

[0097] At the same time, zirconium oxide powder can form a uniform lubricating film between the ingot and the crystallizer, reducing friction, reducing pulling resistance, and facilitating smooth demolding of the ingot, while reducing defects such as scratches and cracks on the surface of the ingot.

[0098] Furthermore, by comparing Example 2 and Examples 4-6, it can be seen that:

[0099] When other components in the protective slag for 2520 heat-resistant stainless steel remain unchanged and the weight of the stabilizer continues to increase, the erosion rate of the protective slag continues to decrease, the slag viscosity is significantly reduced, and the removal rate of inclusions continues to increase.

[0100] Among them, alumina and silica can change the composition of the slag and make it more fluid, because alumina and silica can form a low-melting-point liquid phase, lowering the overall melting point of the slag and thus improving fluidity; during the continuous casting process, an appropriate amount of alumina and silica can form a uniform and stable protective slag film, which helps to evenly distribute the slag between the ingot and the crystallizer, reduce friction, improve the surface quality and dimensional accuracy of the ingot, and optimize the slag distribution and ingot quality during the continuous casting process.

[0101] At the same time, alumina and silica coatings have good adsorption properties and can effectively adsorb non-metallic inclusions in the molten metal, such as oxides, sulfides, etc., thereby improving the purity of the molten metal; the coating can change the density and viscosity of the slag, which helps the inclusions to float in the slag, making it easier to separate from the molten metal and reduce the amount of inclusions remaining in the casting; by efficiently removing inclusions, the coating can improve the metallurgical quality of the final product, reduce internal defects, and improve the mechanical properties and corrosion resistance of the material.

[0102] Specifically, the alumina layer and the silica layer in the stabilizer can also significantly improve the chemical stability and high temperature resistance of the zirconium oxide powder, reduce the erosion of the zirconia powder by molten metal, slag and furnace gas, and the high chemical stability and high temperature resistance of the coating significantly improve the corrosion resistance of the zirconium oxide powder; the alumina layer and the silica layer can form a dense protective layer at high temperature, effectively blocking the penetration of the corrosive medium; and the presence of the composite coating can reduce the thermal shock damage of the zirconium oxide powder and increase its service life in high temperature cycles.

[0103] By comparing Example 6 and Example 7, it can be seen that as the molar ratio of zirconium chloride to yttrium nitrate in the zirconium oxide powder increases, various properties of the mold slag are increased to varying degrees.

[0104] The addition of yttrium can stabilize the cubic or tetragonal crystal form of zirconia by forming a solid solution, avoiding harmful phase changes during heating and cooling; yttrium-stabilized zirconia has good chemical stability and can resist the corrosion of various components in the molten steel, which helps to improve the durability and stability of the protective slag, and the appropriate yttrium content can improve the fluidity of the zirconia powder, which is crucial for the fluidity and covering performance of the protective slag at high temperatures, ensuring that it can effectively isolate the air and prevent oxidation of the molten steel; the increase in the molar ratio of zirconium chloride and yttrium nitrate directly affects these properties of the zirconia powder, and thus affects the functional performance of the entire protective slag.

[0105] Furthermore, by comparing Examples 7-9, it can be seen that as the deposition thickness of the aluminum oxide layer and the silicon dioxide layer increases, the various properties of the protective slag increase to varying degrees.

[0106] A thicker aluminum oxide layer can provide better corrosion resistance because it has higher chemical stability and resistance to acids and alkalis.

[0107] The silicon dioxide layer can provide additional corrosion resistance, especially to alkaline environments. Thicker silicon dioxide layers can further improve corrosion resistance; due to the low melting point and viscosity of silicon dioxide, increasing the thickness of the silicon dioxide layer can further improve fluidity.

[0108] According to the above test experiments, embodiment 8 is taken as the best embodiment;

[0109] By comparing Example 8 with Comparative Examples 1-2, it can be seen that zirconium oxide has a significant effect on the various properties of the protective slag, and the presence of yttrium nitrate in the zirconium oxide powder can control the growth rate of the zirconium oxide particles, which helps to obtain a more uniform and finer particle size. Small and uniform particles are beneficial to improving the sintering properties of the material and the performance of the final product; yttrium ions can enter the zirconium oxide lattice to form a solid solution, stabilizing the cubic or tetragonal phase of the zirconium oxide. Unstabilized zirconium oxide will undergo a transformation from monoclinic phase to tetragonal phase and then to cubic phase at high temperatures, and will reverse during the cooling process. This transformation is accompanied by a change in volume, which may cause the material to crack or degrade in performance. The addition of yttrium can inhibit this phase change and improve the high-temperature stability of the zirconium oxide material; yttrium-stabilized zirconium oxide has better chemical stability and can resist the erosion of other chemical substances at high temperatures, such as oxides and other impurities in molten steel, which is very important in certain specific applications, such as as a refractory material or high-temperature structural material.

[0110] It can be seen from Example 8 and Comparative Example 3 that after removing the alumina and silica coatings in the stabilizer, the slag viscosity of the protective slag increases significantly, which can further prove that alumina and silica can form a low-melting-point liquid phase, reduce the overall melting point of the slag, and thus improve fluidity.

[0111] In summary, a layer of alumina and silica composite coating is deposited on the surface of magnesium oxide, forming a dense physical barrier on the surface of magnesium oxide, which effectively blocks the corrosion of magnesium oxide by harmful components in the slag and significantly improves the corrosion resistance of magnesium oxide; at the same time, the selectivity and permeability of the coating allow magnesium oxide to still react with components in the slag (such as sulfur) when needed, maintaining its activity in desulfurization and impurity removal; alumina and silica have a high melting point and good thermal stability, and the composite coating significantly improves the stability of magnesium oxide at high temperatures, preventing it from decomposing or deteriorating, and the composite protective modified magnesium oxide improves the corrosion resistance, thermal stability and fluidity of the slag, optimizing the overall performance of the slag.

[0112] Furthermore, the alumina and silica coating can form a physical isolation layer between the magnesium oxide and zirconium oxide powders to reduce direct contact between the two. At the same time, it can effectively block the corrosion of magnesium oxide by harmful components in the slag, improve the corrosion resistance of magnesium oxide, and reduce the interface reaction between magnesium oxide and zirconium oxide powders to prevent the formation of undesirable compounds and maintain the purity and uniformity of the protective slag; the alumina and silica composite coating and zirconium oxide powder work together to ensure that magnesium oxide and zirconium oxide powders can remain active at high temperatures and effectively participate in the desulfurization and impurity removal process.

[0113] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A protective slag for 2520 heat-resistant stainless steel, characterized by: The invention comprises the following components: 30-40 parts by weight of calcium oxide, 15-20 parts by weight of aluminum oxide, 8-12 parts by weight of zirconium oxide powder, 5-10 parts by weight of silicon dioxide, 10-15 parts by weight of manganese oxide, 3-5 parts by weight of titanium dioxide, 3-5 parts by weight of calcium fluoride, 8-10 parts by weight of a stabilizer and 3-5 parts by weight of a rare earth element oxide; Wherein, the zirconium oxide powder is prepared by coprecipitation of zirconium chloride and yttrium nitrate; The stabilizer is obtained by depositing aluminum oxide and silicon dioxide on the surface of magnesium oxide; The rare earth element oxide is a mixture of cerium oxide and lanthanum oxide, and the mass ratio of cerium oxide to lanthanum oxide is 2:

1.

2. The protective slag for 2520 heat-resistant stainless steel according to claim 1 is characterized in that: The molar ratio of zirconium chloride to yttrium nitrate is 20-26:

1.

3. The special protective slag for 2520 heat-resistant stainless steel according to claim 1 is characterized in that: In the stabilizer, magnesium oxide accounts for 80-90% by weight of the stabilizer; The molar ratio of alumina to silica is 1.18-1.35:

1.

4. The special protective slag for 2520 heat-resistant stainless steel according to claim 1 is characterized in that: The specific preparation steps of the zirconium oxide powder are: Dissolve zirconium chloride and yttrium nitrate in water; The pH value of the solution is adjusted to within the range of 7.0-7.8 to allow the zirconium and yttrium salts to precipitate simultaneously; Add 14-16M ammonia water at a stirring speed of 360-480rpm to precipitate zirconium and yttrium salts; The precipitate is filtered and washed, and repeatedly washed with deionized water until no chloride ions and nitrate ions remain in the washing liquid; The precipitate was dried in a drying oven at 60-100°C to remove moisture; calcining the dried precipitate in a muffle furnace at 500-800°C for 2-4 hours to remove organic matter and form zirconium oxide powder; Sintered again in a high temperature furnace at 1400-1600°C for 2-4 hours to form a dense zirconia powder.

5. The special protective slag for 2520 heat-resistant stainless steel according to claim 1, characterized in that: The preparation steps of the stabilizer are specifically as follows: S1.1, washing the magnesium oxide particles with deionized water and ethanol multiple times to remove surface contaminants, and then drying them in an oven at 60-100°C; S1.2, dissolving aluminum nitrate in ethanol solvent, and adding citric acid to prepare an aluminum oxide precursor solution; Immerse the magnesium oxide particles in the precursor solution for 45-60 minutes; The magnesium oxide particles are taken out and rinsed with deionized water to remove excess precursor solution; Heat treatment in a muffle furnace at 500-800°C for 2-4 hours to decompose the precursor and form an aluminum oxide coating; S1.3, dissolving tetraethyl orthosilicate in ethanol solvent, adding 15M ammonia water to prepare a silicon dioxide precursor solution; Immerse the magnesium oxide particles on which the aluminum oxide layer has been deposited in the precursor solution for 30-45 minutes; The magnesium oxide particles are taken out and rinsed with deionized water to remove excess precursor solution; Heat treatment in a muffle furnace at 500-800°C for 2-4 hours to decompose the precursor and form a silicon dioxide coating; A stabilizer having a multi-layer composite coating is formed by sequentially depositing an aluminum oxide layer and a silicon dioxide layer.

6. The protective slag for 2520 heat-resistant stainless steel according to claim 5, characterized in that: In S1.2, the amount of citric acid added is 10%-20% of the molar number of aluminum nitrate; The concentration of the alumina precursor solution is 0.2-0.3M.

7. The special protective slag for 2520 heat-resistant stainless steel according to claim 5, characterized in that: In S1.3, the molar ratio of ammonia water to dissolved ethyl orthosilicate is 0.18-0.28:1; The concentration of the silica precursor solution is 0.08-0.15M.

8. The special protective slag for 2520 heat-resistant stainless steel according to claim 5, characterized in that: The aluminum oxide layer has a deposition thickness of 9-12 μm; The silicon dioxide layer is deposited to a thickness of 4-6 μm.

9. A preparation process of a special protective slag for 2520 heat-resistant stainless steel, used for a special protective slag for 2520 heat-resistant stainless steel as claimed in any one of claims 1 to 8, characterized in that: The specific preparation process of the special protective slag for 2520 heat-resistant stainless steel is as follows: According to the content requirements of each component in the protective slag formula, weigh the following raw material components by weight percentage: 30-40 parts by weight of calcium oxide, 15-20 parts by weight of aluminum oxide, 8-12 parts by weight of zirconium oxide powder, 5-10 parts by weight of silicon dioxide, 10-15 parts by weight of manganese oxide, 3-5 parts by weight of titanium dioxide, 3-5 parts by weight of calcium fluoride, 8-10 parts by weight of magnesium oxide and 3-5 parts by weight of rare earth element oxide, and mix the above raw materials evenly; The mixed raw materials are put into a high-temperature furnace to melt and form fluid slag; Pour the molten protective slag into the mold, cool it and solidify it into shape; The solidified protective slag blocks are broken into slag particles, which are sieved through a screen to obtain finished protective slag particles.

10. The process for preparing special protective slag for 2520 heat-resistant stainless steel according to claim 9, characterized in that: The particle size of the finished protective slag particles is 0.28-0.38 mm.

Citation Information

Patent Citations

  • Agent for maintaining surface temperature of molten steel and method for maintaining surface temperature of molten steel

    CN102762320A

  • Preparation method of nano-yttrium-stabilized zirconia-alumina composite powder

    CN109704731A